Utilitarian, hedonic, and social values on e-commerce customer loyalty: mediating role of customer satisfaction - Rendy Indra Yusnara; Soepatini Soepatini (Journal of Enterprise and Development (JED), 2023)
Purpose — The objective of this research is to examine how utilitarian value, hedonic value, and social value influence customer loyalty in e-commerce, as well as to investigate whether customer satisfaction can serve as a mediator.Method — A quantitative research methodology was employed in this study, utilizing students from Soloraya as the population. The primary means of data collection was through the distribution of questionnaires, which were designed using a Likert scale. The study consisted of 105 respondents, and data analysis was conducted using Partial Least Squares (PLS) analysis with SMARTPLS software. PLS-SEM analysis comprises two models: an outer model and an inner model.Result — We found that utilitarian value, hedonic value, and social value had a positive and significant impact on customer loyalty, as well as customer satisfaction. Furthermore, utilitarian value, hedonic value, and social value were observed to have a positive and significant impact on customer satisfaction. In addition, the findings also indicate that customer satisfaction plays a mediating role in the relationship between utilitarian value, hedonic value, social value, and customer loyalty.Contribution — The present study provides valuable insights to the academic community by expanding knowledge in the marketing field, specifically with regards to the influence of utilitarian, hedonic, social value, and customer satisfaction on customer loyalty. Moreover, this study has the potential to make a significant contribution to the advancement of the e-commerce subsector in Indonesia by presenting novel and relevant information.